2019
DOI: 10.5530/pj.2019.11.86
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antioxidant Activity Study of Methanol Extract of Stems and Roots of Codonopsis clematidea from Trans-himalayan Region

Abstract: Aim: The present report aimed to study the therapeutic and phytochemical properties of stems and roots of trans-himalayan plant Codonopsis clematidea. Material and Methods: The crude samples of stems and roots were explored for their chlorophyll, carotenoid and carbohydrate content in order to understand the matrix of these two plant parts. The extraction of phytochemicals was carried out by three different methods viz. sonication, maceration and soxhlet in methanol to identify the best extraction method. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The ABTS cation radical technique was utilized to determine the free radical scavenging potential of the 5a-n and 6a-d. Any compound with antioxidant potential decreases the absorption of the sample solution at 734 nm by scavenging the ABTS radicals. 43 In current findings, it was found that all the synthesized compounds showed antioxidant activity. Out of all the compounds 5a, 5b, 5c, 5g, 5i, 5k, 5n, 6b, 6c, and 6d showed the highest activity.…”
Section: Abts Free Radical Scavenging Assaymentioning
confidence: 67%
“…The ABTS cation radical technique was utilized to determine the free radical scavenging potential of the 5a-n and 6a-d. Any compound with antioxidant potential decreases the absorption of the sample solution at 734 nm by scavenging the ABTS radicals. 43 In current findings, it was found that all the synthesized compounds showed antioxidant activity. Out of all the compounds 5a, 5b, 5c, 5g, 5i, 5k, 5n, 6b, 6c, and 6d showed the highest activity.…”
Section: Abts Free Radical Scavenging Assaymentioning
confidence: 67%
“…Phytochemical screening using GC-MS: the phytochemical analysis was conducted utilizing a Thermo Trace 1300GC gas chromatography system coupled with a Thermo TSQ 8000 Triple Quadrupole MS, following the procedure described by BHARDWAJ & al. (2019), with minor adjustments.…”
Section: Phyto-characterization Of Fruit Extractmentioning
confidence: 99%
“…In order to counter the problem of resistance produced by the present antiviral and antibacterial drugs and owing to the toxic nature of most of synthetic antioxidants or preservatives, from precedent decade, the extensive search for plant based novel antibacterial, antiviral and antioxidants agents is underway [ [7] , [8] , [9] , [10] , [11] ]. Therefore, in the coming future there are innumerable projections to pursuit for the diverse array of natural bioactive antibacterial, antiviral and antioxidant agents of plant origin [ [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%